The History of Czechoslovak / Czech Film in the Mirror of its Economic Data - Czesany Dvořáková, Tereza; Doležalová, Antonie; Moravcová, Hana (Iluminace, 2020)
The study aims to show the potential hidden in the original archive resources of the film industry companies and movies for the economic analysis of the Czechoslovak and Czech film industry in the 20th century in various ideological and economic regimes. The study answers three questions: * how can researchers use the film archive resources for the economic analysis of the film industry; * how can the film archive resources be used for the analysis of the economic decisions of film producers; * what were the economic costs of Czechoslovak and Czech movies from the historical perspective? In the first chapter the study analyses the structure and quality of the gathered data as well as the evolution of budgeting strategies of producers. Based on the collected archive sources, the second chapter provides the first analysis of the structure of financial sources of the three Czech movies - The Son of Mountains (Vladimír Slavínský, 1925), Rosina the Foundling (Otakar Vávra, 1945), and The Party and Guests (Jan Němec, 1966) - that were produced in various periods. At the same time, the second chapter deduces possible strategies used by companies for financing their movies. The third chapter analyses the financial cost of Czechoslovak and Czech movies. The analysis shows that the highest costs happened in the extraordinary last year of the Second World War, and then in the 1950s. With the only exception being 1974 and 1977, the costs in other years did not come close and fluctuated alongside a significantly lower level of today's average cost as declared by film producers. The study is the outcome of the research project "Kolik kdy stál český film", supported by the Czech Film Fund (no 1364/2016).
Keywords: economic analysis; productions studies; Czechoslovakia; average costs; investments; state subsidies